Pengaruh Locus of Control Dan Kecerdasan Spiritual Terhadap Resiliensi Siswa Madrasah Aliyah Negeri Langsa - Putri Balqis; Asih Menanti; Hasanuddin Hasanuddin (Mahesa Research Center, 2022)
This research method uses quantitative methods. The purpose of this study was to determine the effect of locus of control and spiritual intelligence on resilience. The population is 205 students with 8 classes and the sample is 92 with random sampling technique. The results of this study indicate that there is an influence between locus of control and resilience, there is an influence between locus of control and resilience, where the correlation coefficient tx1y = 2.435 with p = 0.017 means p <0.05. The results of this study prove that locus of control has a significant positive effect between locus of control and resilience, where the coefficient tx1y = 2.435 with p = 0.017, this means that the better the locus of control, the better resilience. The coefficient of r squared locus of control with the dependent variable of resilience is r2 = 0.094. This shows that resilience is formed by the locus of control with a contribution of 9.40%. In the spiritual intelligence variable with resilience there is also a significant positive effect between spiritual intelligence and resilience, where the coefficient tx2y = 3.840 with p = 0.000, this means that the better the spiritual intelligence, the better the resilience. The r-squared coefficient of spiritual intelligence with the dependent variable of resilience is r2 = 0.179. This indicates that resilience is formed by spiritual intelligence with a contribution of 17.90%. Similar results come from the interaction effect, there is a significant effect between locus of control, spiritual intelligence and resilience, where the coefficient F = 16,738; with p = 0.000 means p < 0.050. The determinant coefficient (r2) of the influence between predictors of locus of control, spiritual intelligence with the dependent variable resilience is r2 = 0.273. This shows that resilience is formed by locus of control and spiritual intelligence together with a contribution of 27.30%.